“Tinged with gloom and grandeur”: Romanticism, Conservatism & Upper Canadian Political Culture - McKim, Denis (Ontario History)

(untitled) (The Ontario Historical Society, 2022)
Scholars have discussed the role of romanticism in the condescending attitudes of Upper Canadian conservatives toward Indigenous peoples but they have yet to examine its role in the political culture of settler society; specifically, as it applies to the political ideology of Tories, the group that prevailed in bustling towns and embryonic outposts alike. Weaving together intellectual history, the history of emotions, and environmental history, this article explores the romantic tradition’s salience within the mentalité of Upper Canadian conservatism. It contends that influential figures from the worlds of politics and literature repeatedly invoked aspects of romanticism over several decades in denouncing subversive phenomena and in seeking to legitimize their vision of a hierarchical society. In particular, they drew on such compelling romantic tropes as powerful emotions and the magnificence of nature in the hope of bolstering a social order predicated on elite hegemony and rank-and-file deference. This helps to shed light on one of the animating factors within the Tory tradition, a multifaceted force that, for good or ill, has played an important role in shaping Ontario’s history.